Analysis The Integration of The Criminal Justice System in Handling Corruption - Husin, Nabilla Callosa (Corruptio, 2024)
Corruption as a serious crime has detrimental effects on the state and society. One of the solutions to overcome corruption is by implementing an integrated criminal justice system that involves law enforcement agencies, such as the police, prosecutors and judges. Enforcement of the criminal justice system must be based on the KUHAP as the mouthpiece of the law for the Police and Prosecutor, meanwhile, the KPK is not only based on the KUHAP but also on Law Number 19 of 2019 jo. Law Number 30 of 2002 on The Corruption Eradication Commission (KPK). The synergy that is expected in the context of overcoming criminal acts of corruption in the context of the criminal justice system turns out to still contain law enforcement problems in it, such as the substance of the law, overlapping authority, independence, weak coordination, human resources, and the lack of optimality of the special criminal justice system.